PENGARUH KECERDASAN EMOSIONAL DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA PEMERINTAHAN KECAMATAN SIBOLGA SAMBAS - Azhari Hasbi; Mansur Tanjung; Yusi Tri Utari Panggabean (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2023)
Human resources are one of the important factors in an organization, both agencies and companies. One of the most important resources for the world of work or agencies is a human being who is an employee, employee, laborer or worker. One of the factors that affect employee performance is emotional intelligence. Another factor that affects employee performance is work motivation. This study aims to determine the effect of emotional intelligence and work motivation on employee performance in the District Government of Sibolga Sambas.The type of research used in this study is a research approach using descriptive methods, namely research carried out by collecting data according to the actual situation with the aim of revealing facts and seeking information about the causes of the problem and how to solve it. Descriptive method, Quantitative is a method used to make a broader conclusion. Based on the partial hypothesis test, it is known that emotional intelligence has an effect on employee performance. This research can be seen from the calculation results obtained from the T test, namely the known value of Sig. for the effect of X1 on Y is 0.002 <0.05 and the value of T count is 3.291 > 1.999 so it can be concluded that H1 is accepted which means that there is an influence of Emotional Intelligence on Employee Performance. Employee Performance. This research can be seen from the calculation results obtained from the T test, namely the known value of Sig. for the effect of X2 on Y is 0.032 <0.05 and the value of T count is 2.197 > 1.999 so it can be concluded that H2 is accepted which means that there is an effect of X1 on Y1. Based on the F test, it is known that the value of Sig. for the simultaneous influence of Emotional Intelligence and Work Motivation on Employee Performance is 0.001 < 0.05 and the F value is 10.192 > F table 3.31 So it can be concluded that H3 is acceptable, which means that there is an influence of Emotional Intelligence and Work Motivation simultaneously on performance Employee.